Maqashid Sharia Index: Reviewing The Financial Performance Of Sharia Banks In Indonesia During The Outbreak - Prahara, Rahma Sandhi; Sundari, Sundari; Andayani, Hirini; Diah Syifaul (Jurnal Ekonomika dan Bisnis Islam, 2023)
In the era of global economic crisis due to the outbreak, according to data obtained from the Financial Services Authority, the total assets of Islamic banking show a positive trend as the assets increase every year. This study aims to assess the performance of Islamic banking in Indonesia before and after the Covid 19 pandemic using the Maqashid Syariah Index (MSI) approach. There are three indicators used in the measurement, namely individual education, the embodiment of justice and the general benefit. Using purposive sampling technique, five Islamic banks with the largest office network, Bank Muamalat Indonesia (BMI), BRI Syariah Bank (BRIS), Mega Syariah Bank (BMS), BJB Syariah Bank (BJBS) and BCA Syariah Bank (BCAS), were selected in which the annual report data were analyzed by using SAW (Simple Additive Weighted). The results of this study indicate that based on the calculation of the Maqashid Syariah Index, there are two Islamic commercial banks in which the financial performance has increased during the pandemic, while the others experienced a decline after the pandemic